Pengaruh Kualitas Produk, Harga, Dan Pelayanan Purna Jual Lampu Merk Hori Terhadap Keputusan Pembelian PT. Fokus Dayautama Di Jakarta Timur - Rahadian Ananto; Suadi Sapta Putra; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of product quality, price, and after-sales service on purchasing decisions of Hori Brand Lamps at PT. Fokus Dayautama in East Jakarta. The population of this study is the consumer of Hori Brand Lights in Jakarta in this study is not known with a sample of 96 workers who handle the installation of street lights by the Department of Highways and Sub-departments based on Anderson's formula. This study uses primary data with data collection methods through questionnaires distributed to 96 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results obtained in this study are product quality has a positive effect on purchasing decisions, price has a positive effect on purchasing decisions and after-sales services have a positive effect on purchasing decisions. Therefore, PT Fokus Dayautama East Jakarta should pay attention to product quality, price, and after- sales service for Hori Brand Lamps on purchasing decisions. Keywords: Product Quality, Price, After Sales Service and Purchase Decision.